Features of road safety project implementation until 2024 in Omsk region - E. A. Safronov; K. E. Safronov (Вестник СибАДИ, 2021)
Introduction. One of the important problems in the Russian Federation is road safety improvement (RS). This is due to the enormous damage that accidents inflict on the national economy. The Russian Federation lags behind the leading countries of the European Union in the field of road safety in terms of key indicators by 3.5 times. To close the gap, in January 2018, we adopted the 'Strategy for road safety in the Russian Federation for 2018 - 2024’ (Strategy). The goal of the Strategy is to strive for zero mortality in road traffic accidents (RTA) by 2030, and in 2024 to reduce the social risk to 4 deaths per 100 thousand inhabitants.Materials and methods. The developments are based on a new theory developed at SibADI - this is the cyclical dynamics of road accidents on a national scale, subordinate to the level of the economy. During crisis, there is a decrease in the number of accidents; this is influenced by a number of factors, the main one is a decrease in the total mileage of vehicles. During such periods, the effectiveness of measures to reduce road accidents is often confused with the real cause, which leads to a decrease in funding and the curtailment of work to improve road safety, which should not be done. When the economy recovers, the level of road accidents recovers and even begins to grow due to the loss of qualifications of drivers who are idle during the crisis.Results. There are two different approaches to achieving this goal. At the federal level, there is a programmatic approach, while in the regions the project method is used within the framework of the 'Safe and High-Quality Highways’ national project (BKAD). A similar project was adopted in the Omsk region. A feature of the road safety project implementation in the Omsk region is the involvement of science. Research is carried out at the Organization and Traffic Safety Department and is introduced into the educational process and implemented at the Federal Training Center for advanced training of workers involved in the training of drivers, created in SibADI.Discussion and conclusion. The scientific approach guarantees the identification and quality solution of the main problems of the road safety project. This applies to recommendations for stabilizing project financing, justifying the development of public transport, using new technologies, improving the regulatory and legislative framework in all areas of urban planning and infrastructure.